(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article addresses encryption algorithms based on the application of quantum particle physics rather than mathematical techniques, as well as the challenges that traditional cryptography approaches will encounter with the development of quantum computers. An overview of the most recent algorithms for quantum cryptography is given. The benefits and drawbacks of the suggested quantum algorithm-based information protection techniques are examined.